Prevalence, correlates, and trends of intimate partner violence against women in Sierra Leone: findings from 2013 and 2019 demographic and health surveys - Shaikh, Masood Ali (Frontiers in Public Health, 2023)
Background: Intimate partner violence (IPV) is a globally pervasive public health and medical problem in addition to being a repugnant violation of women's' rights. The objectives of this study were to analyze the lifetime prevalence and correlates of IPV perpetrated by either current/former husbands/partners of ever-married women aged 15-49 years, using the most recent nationally representative Sierra Leone Demographic and Health Survey (DHS) conducted in 2019. Ethnicity-based levels and trends of IPV were computed using the data from the DHS conducted in 2013 with 2019 DHS. Methods: Twelve IPV correlates pertaining to socio-demographic, attitudinal, and experiential attributes were analyzed in bivariate and multivariable models, using logistic regression. IPV was computed as a composite variable comprising of physical, emotional, and/or sexual IPV. Results: The lifetime prevalence of having ever experienced any type of IPV was a staggering 60.81%; while emotional, physical, and sexual IPV prevalence were reported by 45.90%, 49.81%, and 8.14% respondents, respectively. No ethnicity reported statistically significant decrease in any type of IPV during the intervening period between the two surveys. Five out of nine ethnicities reported statistically significant increase in emotional IPV. While few ethnicities reported statistically significant increase in one or more types of IPV. Conclusion: The high lifetime prevalence of IPV is alarming and augurs the need for targeted health education and promotion activities to stem and reverse the tide of IPV in Sierra Leone, including endeavors focusing change in cultural and ethnicity-based norms and mores to ensure women's human rights are respected and upheld.